Study of perinatal outcome in human immunodeficiency virus positive women - Gautam, Shiva; Shah, Tushar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: HIV remained a major public health problem in developing countries like India. Young adults especially women of reproductive age group are mainly affected. HIV is caused by human immune deficiency virus which decreases host immunity and leads to opportunistic infections. The aim of this study is to know the perinatal outcome of HIV positive women and the complications occurring in perinatal period leading to mortality. Methods: It is a retrospective study done for 2 years from September 2013 to September 2015. Data was collected from PPTCT centre civil hospital Ahmedabad retrospectively from records only. Identity of patients was not disclosed. Results: Among total 65 patients who were followed up 82.53% new-born were healthy and 10.99%were having morbidity factors. Causes of morbidity were low birth weight, IUGR, septicemia, jaundice etc. Hypoxemic ischemic encephalopathy is the most common cause of neonatal mortality and septicemia being second. Conclusions: Maximum new-born were healthy. Hypoxic ischemic encephalopathy is the leading cause of neonatal death. Because of newer WHO guidelines of starting ART to all antenatal women, improved PPTCT counseling and better NICU facility neonatal outcome has improved.